Plant mite (Acari) diversity in three regions of Ecuador - Ortega Ojeda, Carlos Alberto (2022)
As concluded by recent studies, to disregard the invertebrates and include basically just birds and mammals in the IUCN (International Union for Conservation of Nature) Red List would be ignoring the apparently evident sixth mass extinction. This reality is what makes studies about biodiversity so important and useful as “preventive archaeology”, by collecting and documenting as many species as possible before they disappear. Ignoring this situation is like doing nothing, denying the crisis, or accepting it inconveniently, leading the planet inevitably towards that alerted new mass extinction, the sixth. This certainty and the primary need to know the diversity of the Ecuadorian mites, to defend and promote it, have motivated the present study, which after being carried out as a prospection, will be the basis for a larger one, which systematically leads to determine the Ecuadorian mite diversity, continental and insular. With this background, a systematic survey of the diversity of the subclass Acari was carried out in the northern region of Ecuador, in small and medium sized farms, on wild and cultivated plant species. There were identified 2,257 mites from nineteenfamilies, corresponding to the orders Mesostigmata and Trombidiformes, including possible new records for the country and new species, one of which was published as Amblyseius yumbus Ortega-Ojeda, Santos, Melo-Molina and Moraes 2021, mite with potential for predation of phytophagous mites.